Diplomatic Leadership and its Role in Mitigating Organizational Disturbances: A Study of the Opinions of a Sample of Staff at the Al-Diwaniyah Municipality - Al-Nawfal, Sultan Ahmad Khulayf; Al-Hilali, Hasan Idnayn Abd Ali (Indian Journal of Information Sources and Services, 2025)
The current study aims to uncover the role of diplomatic leadership through its dimensions, which include (mastering Mastering the Arts of Negotiation, openness, diplomatic language, flexible communication, representing and defending interests), in Mitigating organisational disturbances manifested in (limiting behavioural disturbances, Mitigating psychological disturbances, avoiding procedural disturbances) among a sample of staff members in the Diwaniya Municipal Directorate. The issue of the study stemmed from the following question: Is there a role for diplomatic leadership in mitigating organisational disruptions at the Diwaniya Municipal Directorate? The study hypothesis was formulated according to the following context: There is a correlation and impact between diplomatic leadership and the reduction of organisational disruptions at the level of the Diwaniya Municipal Directorate. The questionnaire was adopted as the primary tool for measuring the level of the current study's variables through their dimensions and the items expressing them. A total of 150 questionnaires were distributed, of which 137 were returned, with 13 being damaged and 124 valid for analysis. The study relied on two software packages for analysis (SPSS and AMOS) to extract the levels of the study variables and dimensions, and the descriptive approach was adopted. The study yielded several results, the most significant of which was the existence of a significant correlation and impact between diplomatic leadership and the reduction of organisational disturbances at the level of the Diwaniya Municipal Directorate.